Formulation and characterization of palm oil ester-based betamethasone 17-valerate creams and comparison with marketed products - Win, Thazin; Ahmad, Kausar; Md. Jaffri, Juliana; Edueng, Khadijah (2014)
This study aimed to formulate and characterize betamethasone 17-valerate creams produced from palm olein-based oil-in-water emulsions and compare the data to that of commercial products. Test creams with three different viscosities were prepared using varying concentrations (0.1, 0.2 and 0.3% w/w) of Carbopol®940 as thickener, palm olein as oil phase, Span®20/Tween®20 as surfactants, parabens and chlorocresol as preservatives, propylene glycol as solubilizer, betamethasone 17-valerate as active ingredient and distilled water as aqueous phase. Control creams were prepared without drug to investigate the effect of the drug on vehicle. Three marketed creams containing same active ingredient were purchased from local pharmacy for comparison purpose. All formulations were characterized for particle size, viscosity, rheology, phase separation, pH and zeta-potential for one year. Statistical analysis was performed with MINITAB® (version 16.1) software. The optimized formulations showed particle size range 2 to 14 μm, viscosity 100 ± 0.57 mPa.s, yield stress 35.6 ± 4.6 Pa, thixotropy 789 ± 1.15, pH 5.0 ± 0.2 and zeta potential -68.36 ± 1.06 mV. In comparison, the commercial creams had larger particle sizes and slightly higher viscosities. However, test creams had greater electrophoretic stabilities than marketed creams as the latter had lower zeta potential values (13.02 ± 0.78 mV). Moreover, betamethasone 17-valerate did not affect the properties of vehicle as the results of control creams were not greatly different from that of test creams. From these results, it was concluded that palm-olein-in-water emulsion could be alternative vehicle for topical drug delivery of lipophilic drugs.